The Oligocene Maikop series of Lahich (eastern Azerbaijan): paleoenvironment and oil-source rock correlation - Bechtel, Achim; Movsumova, Ulviyya; Pross, Jörg; Gratzer, Reinhard; Ćorić, Stjepan; Sachsenhofer, Reinhard F. (Organic geochemistry, 2014)
The Maikop Formation, deposited in eastern Azerbaijan during Oligocene and Early Miocene, represents a prolific source unit for the oils found within the southern Gobustan area and the Kura Depression. Based on biomarker characteristics, the oils are believed to have originated from a clastic source rock deposited in an anoxic to suboxic, transitional marine environment with low to moderate input of terrigenous organic matter. However, due to the thermal immaturity of accessible Maikop rocks, oil-source rock correlation based on biomarker fingerprints is hampered. The results from a sedimentary succession sampled in the Shemakha-Gobustan area near the village of Lahich revealed the presence of marginally mature (Rr=0.6-0.7%) Maikop rocks. Based on lithology, geochemical data and paleontological analyses, the sampled section contains Upper Eocene and Lower Oligocene sediments. Palynological analyses of dinoflagellate cysts indicate an early Rupelian to early Chattian (Oligocene) age for the upper part of the investigated Maikop succession. However, the stratigraphic position of the middle and lower part of the succession remains unclear. Maceral composition, as well as biomarker and stable isotope (C, N) data indicate a major contribution of aquatic organisms and variable inputs from macrophytes and land plants to organic matter deposition during the Oligocene. Microbial communities most probably included heterotrophic bacteria and cyanobacteria, as well as green sulfur bacteria. Higher inputs of terrigenous organic matter occurred during deposition of the lower part of the succession. Increased remineralisation of organic matter in the water column is suggested to result in low TOC and hydrocarbon contents, as well as 15N enriched total nitrogen of the Eocene to earliest Oligocene sediments. Organic carbon accumulation during the Oligocene occurred in a stratified, episodically euxinic environment. This is indicated by low TOC/S ratios and higher contents of aryl isoprenoids in several samples from the upper units. A moderate to good oil-source rock correlation with oils from the Kura Depression is indicated by sterane and triterpane fingerprints as well as carbon isotopic composition of hydrocarbon fractions.